Relationship between bioethics and life sciences research in Argentina: Descriptive study at national level - Sánchez Thevenet, Paula; Javaloyes del Río, Carmen (Acta Bioethica, 2011)
The aim of this study is to explore and update the relationship between bioethics and life sciences research in Argentina at national level. For this a descriptive, transversal, content analysis and bibliometric section study was carried out about observable public products of national character. Bioethical elements were found in national norms related to scientific research in this science field. It was evident that the ethical requirements asked in scientific research for the publication of studies in these sciences needs optimization. The contribution of Argentinean authors to bibliography production in the discipline was established since 1988. Results indicate situations that contribute to a consolidation of bioethics discipline in relation to life sciences in Argentina.